System engineering approach to planning anticancer therapies. (2016) - Świerniak, Andrzej; Kimmel, Marek, 1959-; Śmieja, Jaroslaw; Puszynski, Krzysztof; Psiuk-Maksymowicz, Krzysztof
No abstract available